Le beau Serge [videorecording (DVD)] - Chabrol, Claude, 1930-2010; Brialy, Jean-Claude; Blain, Gérard; Meritz, Michèle (Criterion collection (DVD videodiscs), 2011)
When François returns home to his small provincial village, he finds himself at odds with his childhood friend Serge who is now an alcoholic and unhappily married.